Sistem Manajemen Pengetahuan Berbasis Standar Operasional Prosedur Untuk Meningkatkan Kinerja Pegawai - Hartini Hartini (JSINBIS (Jurnal Sistem Informasi Bisnis), 2014)
Application of knowledge management in the company becomes a fundamental requirement in the era of globalization. Company's ability to manage the knowledge that there is a force that is needed to increase competitiveness. Managing knowledge in companies is not easy, because not everyone can share knowledge with other people or companies. The research aims to implement Knowledge Management System based SOP for an organization that is expected to manage organizational knowledge well and easy to perform knowledge sharing. Knowledge Management System is used to support the sharing of knowledge, ie tacit knowledge and explicit knowledge is based on the Standard Operating Procedure. The system is built with moodle as one of the tools Content Management System. Analysis of the conditions of knowledge in organizations is done by using meode Focus Group Discussion. KMS is built can be used to facilitate the process of capturing  the knowledge, store, call and reuse knowledge. By applying this system management processes / documentation can be accommodated with a good knowledge and can be used to improve the performance of the employee.   Keyword : Knowledge Management,Moodle, SOP, Tacit knowledge, Explicit Knowledge